Progressive business an intellectual history of the role of business in American society - Christiansen, Christian Olaf 1980- (Oxford University Press, 2015)
Today, an increasing number of researchers, citizens, politicians, civil organizations, activists, and corporations are concerned with questions such as: Can the financial rationality of firms be constrained by social concerns? Can the market be reformed 'from within'? Starting in the post-Civil War period of American industrialization, the book traces the emergence of ideas about reforming businesses in the American context, and the ideological and intellectual disputes about these ideas. This book offers a new historical, critical, and in-depth understanding of ideas that have today become increasingly widespread in debates about: corporate social responsibility, corporate philanthropy, corporate citizenship, social entrepreneurship, creating shared value, doing business and being virtuous at the same time. What underlies this discourse is the claim that corporations can change from 'within' - reforming themselves into being good citizens of society. While there has been much enthusiasm about ideas of restructuring the corporation, and the relationships between business and society, critics have argued that businesses continue to focus exclusively on making money.